Terahertz Spectral Signatures of Ultrafast Spin Transports in Ferromagnetic Heusler Alloy. Issue 2 (9th January 2023) - Jin, Zuanming; Guo, Yingyu; Peng, Yan; Zhang, Zeyu; Pang, Jinyi; Zhang, Zongzhi; Liu, Fan; Ye, Bin; Jiang, Yexin; Ma, Guohong; Zhang, Chao; Balakin, Alexey V.; et al.
Abstract: Although the Co‐based Heusler compounds are predicted to be half‐metals, their sub‐picosecond demagnetization dynamics upon laser excitation show a transition‐metal‐like behavior. Any possible role of ultrafast nonlocal spin transport on the ultrafast demagnetization of half‐metallic Heusler compounds has only been inferred indirectly by time‐resolved magneto‐optical Kerr effect. Here, an ultrafast optically driven spin current traveling from Co2 FeSi half metal into an adjacent Pt layer by using terahertz (THz) emission time‐domain spectroscopy (TDS) is demonstrated. By varying the magnetic field and excitation symmetry, the sizable THz generation from Co2 FeSi/Pt stack arises from optically induced spin transport across the Co2 FeSi/Pt interface in conjunction with spin‐to‐charge current conversion, via the inverse spin Hall effect (ISHE). The chemical ordering, interface roughness and magnetization of the samples become vital to engineer the THz emission properties. The amplitude of THz emission is comparable to that of CoFeB/Pt stack, thereby indicating Co2 FeSi as an efficient ultrafast light‐driven spin current injector. Finally, by varying the pumping energy, the contributions are distinguished to the ultrafast spin current from thermalization and optical excitation of majority spins in Heusler alloy. This work illustrates THz emission TDS as a powerful tool to investigate the ultrafast spintronic properties of Heusler alloy/normal‐metal bilayers. Abstract : The signature of ultrashort laser driven spin‐dependent transport in the Co2 FeSi interfaced with a Pt layer is imprinted on the terahertz emission. THz spin currents in Co2 FeSi/Pt can be engineered by chemical ordering, interface roughness, and magnetization. Finally, the contributions are distinguished to the ultrafast spin currents from thermalization and optical excitation of majority spins in Heusler alloy.